2006
DOI: 10.1159/000097384
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine and Hematological Factors in Patients with Venous Thromboembolic Diseases in Kuwait

Abstract: Background: Venous thromboembolic disease (VTE) is a common cause of morbidity in Kuwait, but the risk factors have not been studied. Hyperhomocysteinemia has been suggested as one of the risk factors. We postulate that hyperhomocysteinemia acts synergistically with hematological variables to increase VTE risk. This study evaluates the roles of hyperhomocysteinemia and hematological variables in patients with VTE. Methods: We measured fasting plasma total homocysteine (tHcy), activated protein C resistance, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(31 reference statements)
0
3
1
Order By: Relevance
“…24 In this study, the prevalence of hyperhomocysteinemia is found to be higher than the prevalence that was presented in several previous reports that varied between 7.9% and 25% in patients with VTE. 25 27 As well, the mean plasma total homocysteine level of the control group was slightly higher than some of the previous reports, which showed plasma homocysteine levels between 10 and 12 µmol/L in Turkish healthy individuals. 28,29 There may be several reasons for the higher plasma homocysteine levels in our patient and control study population.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…24 In this study, the prevalence of hyperhomocysteinemia is found to be higher than the prevalence that was presented in several previous reports that varied between 7.9% and 25% in patients with VTE. 25 27 As well, the mean plasma total homocysteine level of the control group was slightly higher than some of the previous reports, which showed plasma homocysteine levels between 10 and 12 µmol/L in Turkish healthy individuals. 28,29 There may be several reasons for the higher plasma homocysteine levels in our patient and control study population.…”
Section: Discussioncontrasting
confidence: 63%
“…Our results are in accordance with previous reports that observed an increased risk of VTE in hyperhomocysteinemia between 2.1-and 5.6-fold. 26,36 Another interesting result of the current study is the increased levels of plasma homocysteine among patients with PE compared with DVT (23 + 13.7 vs 16 + 5.8; P < .05). There is limited data comparing plasma homocysteine levels among patients with DVT and PE in the current literature.…”
Section: Discussionmentioning
confidence: 58%
“…The two markers appeared to perform similarly, with a trend toward better performance of serum folate ( Table 1 ). Regression against homocysteine Marouf et al [ 60 ] Men with venous thromboembolism 91 Significant Not significant Marouf et al [ 60 ] Women with venous thromboembolism 110 Not significant Not significant Cheng et al [ 53 ] General population 130 Significant Not significant Dierkes et al [ 61 ] General population 336 Significant Significant Golbahar et al [ 56 ] Subjects with coronary artery disease and matched controls In our own analysis, we investigated the ability of serum and red cell folate to predict elevated plasma homocysteine levels ( ≥ 15 μ mol/L) in 320 randomly selected patient samples sent to our hospital laboratory. Among patients with a normal serum vitamin B 12 concentration and eGFR, serum folate demonstrated a significantly higher area under the receiver operating characteristic curve (AUC) for predicting increased plasma homocysteine concentration.…”
Section: Prediction Of Hyperhomocysteinaemiamentioning
confidence: 99%
“…Though our MR data does not show a significant association between high level with VTE, the p -value is around the border of suggestive significance ( p = 0.078) and suggested a trend toward increasing VTE risk. Likewise, there is no indication of elevated homocysteine in increasing the VTE risk, which suggested that the association seen between homocysteine and VTE might be due to confounders ( 45 ).…”
Section: Discussionmentioning
confidence: 99%